The Tubulin Inhibitor VERU-111 in Combination With Vemurafenib Provides an Effective Treatment of Vemurafenib-Resistant A375 Melanoma - Cui, Hongmei; Wang, Qinghui; Miller, Duane D.; Li, Wei (Frontiers in Pharmacology, 2021)
Melanoma is one of the deadliest skin cancers having a five-year survival rate of around 15–20%. An overactivated MAPK/Akt pathway is well-established in BRAF mutant melanoma. Vemurafenib (Vem) was the first FDA-approved BRAF inhibitor and gained great clinical success in treating late-stage melanoma. However, most patients acquired resistance to Vem within 6~9 months. Therefore, developing a new treatment strategy to overcome Vem-resistance is highly significant. Our previous study reported that the combination of a tubulin inhibitor ABI-274 with Vem showed a great synergistic effect to sensitize Vem-resistant melanoma both in vitro and in vivo. In the present study, we unveiled that VERU-111, an orally bioavailable inhibitor of α and β tubulin, is highly potent against Vem-resistant melanoma cells. The combination of Vem and VERU-111 resulted in a dramatically enhanced inhibitory effect on cancer cells in vitro and Vem-resistant melanoma growth in vivo compared with either single treatment. Further molecular signaling analyses demonstrated that in addition to ERK/AKT pathway, Skp2 E3 ligase also plays a critical role in Vem-resistant mechanisms. Knockout of Skp2 diminished oncogene Akt expression and contributed to the synergistic inhibitory effect of Vem and VERU-111. Our results indicate a treatment combination of VERU-111 and Vem can overcome Vem-resistance for melanoma patients harboring BRAF (V600E) mutation.